The value of sorghum distillers dried solubles in protein feed mixtures when fed as a supplement to shelled corn for fattening spring pigs on alfalfa pasture. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2012)
In recent years much attention has been given to the feeding of distillers by-products to livestock. One of these distillers dried soluble derived from the malting of various grains. In addition to other nutrients, it furnishes some of the B vitamins that have lately been show to be important in swine feeding.
Keywords: Swine; Sorghum; Protein; Alfalfa